Preferences for Capturing Market Share of Halal Products in the 5.0 Era Through the UTAUT-3 Model for MSMEs in Lhokseumawe City - Maulana, Nora; Safwan, Safwan (Al-Muamalat: Jurnal Ekonomi Syariah, 2025)
The purpose of the study was to find a new model in the development of MSMEs and identify a number of important factors that influence the increase in the halal market share of MSMEs through empirical testing of the Unified Theory of Acceptance and Use of Technology (UTAUT-3). The study used a mixed method sequential explanatory technique. The sample was selected using a purposive sampling technique and obtained 70 respondents. Data were collected through questionnaires, interviews, observations and documentation. Quantitative data analysis was carried out using the Partial Least Squares Structural Equation Modeling (PLS-SEM) statistical test. The qualitative analysis was studied using the triangulation technique and continued with the Analytical Network Process (ANP) method. The research findings showed that all independent variables including performance expectations, business expectations, social, facilitating conditions, hedonic motivation, price value, habits, and personal innovation had a significant positive effect on behavioral intentions to use QRIS on MSME actors in Lhokseumawe City. The findings identified that to achieve optimal business rates, more intensive and comprehensive use of digital technology is needed. Through the adoption of QRIS digital technology, strengthening halal branding, product innovation, and increasing competitiveness in order to build partnerships with various stakeholders in creating a halal MSME ecosystem. It is important to have government policies and programs related to development, and creating an ecosystem that supports MSMEs in using technology and promoting halal products in the 5.0 era.